The legal regime and social function of the right to slab (Revista do Tribunal Regional Federal da 3ª Região, 2022)
This article examines the treatment given by Brazilian law to slab law. The slab was born as a spontaneous social phenomenon in the scope of Brazilian favelas, in a precarious and informal way. Clandestineness brought legal uncertainty resulting from the absence of a formal address. There was a need to insert these habitations in the formal system of titles in order to rescue the dignity of such individuals through their allocation in the city and also to convert this dead capital into financial assets in order to encourage economic development. The social fact of the slab was standardized through Provisional Measure nº 759/2016, later converted into Law nº 13.465/2017 and regulated by Decree nº 9.310/2018, thus creating, the real slab right, so as to give visibility to what has always been invisible. Therefore, considering the pluralization of the relations of belonging that emerge from the Federal Constitution of 1988, the real right of slab appears as a new model of autonomous property and totally detached from the soil.
Keywords: Property; urban land regularization; slab law; social function; public policy